Self-Stigma as The Trigger of Depression Factor in Multidrug - Resistant Tuberculosis (MDR-TB) Patients at a Public Hospital in Gresik - Widya Lita Fitrianur; Wiwik Widiyawati; Ervi Suminar (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Multidrug-Resistant Tuberculosis (MDR-TB) is a chronic infectious disease that can affect the patient's physical appearance so that it has an impact on the patient's psychosocial condition, including the emergence of anxiety and depression. Anxiety and depression in MDR-TB patients have an impact on the patient's rejection of the diagnosis and they choose to stop the treatment process. The incidence of anxiety and depression in MDR-TB patients is influenced by several factors, one of which is self-stigma. The purpose of this study was to determine the impact of the factor of self-stigma on the incidence of depression in MDR-TB patients.Method: The study design used a cross-sectional approach with a sample of 71 MDR-TB patients undergoing treatment. The study used a questionnaire that was filled out directly by the patient during the treatment process. The sampling technique used purposive sampling by setting inclusion criteria. The bivariate statistical test used in the study was chi-square.Results: The results of the self-stigma study obtained a p-value = 0.000 <0.05 with an OR value of 54.643, meaning that there was a significant relationship between self-stigma and depression in MDR-TB patients.Conclusions: MDR-TB patients with high self-stigma have a higher chance of experiencing depression than patients with low self-stigma. Suggestions in this study are that it is hoped that the family, health workers, community, and government can help reduce the stigma against patients with MDR-TB. Promotive efforts by providing support and education to the community can help to eliminate the stigma so that the incidence of depression in MDR-TB patients can be minimized.